2017
DOI: 10.1002/pro.3141
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical characterization of the nucleoside hydrolase from C. elegans reveals the role of two active site cysteine residues in catalysis

Abstract: Nucleoside hydrolases (NHs) catalyze the hydrolysis of the N-glycoside bond in ribonucleosides and are found in all three domains of life. Although in parasitic protozoa a role in purine salvage has been well established, their precise function in bacteria and higher eukaryotes is still largely unknown. NHs have been classified into three homology groups based on the conservation of active site residues. While many structures are available of representatives of group I and II, structural information for group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…S6). However, the typical conserved residues known to be involved in the coordination of the pyrimidine or purine moieties in the characterized enzymes among the family are not present (45). As queuosine is a 7-deazaguanine carrying a cyclopentenediol ring linked at position 7 through an aminomethyl linkage, a more sizeable substrate pocket to accommodate the queuine moiety is required.…”
Section: Resultsmentioning
confidence: 99%
“…S6). However, the typical conserved residues known to be involved in the coordination of the pyrimidine or purine moieties in the characterized enzymes among the family are not present (45). As queuosine is a 7-deazaguanine carrying a cyclopentenediol ring linked at position 7 through an aminomethyl linkage, a more sizeable substrate pocket to accommodate the queuine moiety is required.…”
Section: Resultsmentioning
confidence: 99%
“…Others, for example the protozoan GI-nucleoside hydrolase, strongly prefer 6-oxypurine leaving groups, and the IAG-nucleoside hydrolase from T. brucei prefers these purine leaving groups. In contrast, AMP nucleosidase is specific for adenine, and purine nucleoside phosphorylase is specific for 6-oxypurine leaving groups …”
Section: Nucleoside Hydrolasesmentioning
confidence: 98%
“…In contrast, AMP nucleosidase is specific for adenine, and purine nucleoside phosphorylase is specific for 6-oxypurine leaving groups. 85…”
Section: Biological Functionmentioning
confidence: 99%
“…Based on the nature of the active-site residues that are present in the β3-α3 loop (His vs. Trp in group I and II NHs) and before the last Asp in the Ca 2+ coordination sphere (again a His in group I vs. a Trp in group II), a third structural group was anticipated. Indeed, a group of NH proteins from metazoa including C. elegans and X. laevis display a Cys residue rather than Trp260 or His241 [ 33 , 71 ]. Structural characterization of the C. elegans NH showed that it shares the highest catalytic similarity to group II NHs, but displays an overall structure that is more similar to group I NHs, including its tetrameric quaternary structure [ 71 ].…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, a group of NH proteins from metazoa including C. elegans and X. laevis display a Cys residue rather than Trp260 or His241 [ 33 , 71 ]. Structural characterization of the C. elegans NH showed that it shares the highest catalytic similarity to group II NHs, but displays an overall structure that is more similar to group I NHs, including its tetrameric quaternary structure [ 71 ]. Site-directed mutagenesis demonstrated that the Cys residue is involved in the leaving-group activation, albeit through a yet-unidentified mechanism.…”
Section: Reviewmentioning
confidence: 99%